2006
DOI: 10.1139/y06-056
|View full text |Cite
|
Sign up to set email alerts
|

The role of caspase-3 in lipopolysaccharide-mediated disruption of intestinal epithelial tight junctions

Abstract: The mechanisms responsible for microbially induced epithelial apoptosis and increased intestinal permeability remain unclear. This study assessed whether purified bacterial lipopolysaccharide (LPS) increases epithelial apoptosis and permeability and whether these changes are dependent on caspase-3 activation. In nontumorigenic epithelial monolayers, Escherichia coli O26:B6 LPS increased apoptosis, as shown by nuclear breakdown, caspase-3 activation, and PARP cleavage, and induced disruption of tight junctional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 41 publications
3
68
0
Order By: Relevance
“…More specifically, it has been demonstrated that tight junctional proteins, ZO-1 and ZO-2 and occludin, are cleaved by caspase-3 [15]. The role of apoptosis in the potential increase of the BBB permeability by H. parasuis remains to be investigated, with the use, for example, of transwells as previously described [6].…”
Section: Discussionmentioning
confidence: 95%
“…More specifically, it has been demonstrated that tight junctional proteins, ZO-1 and ZO-2 and occludin, are cleaved by caspase-3 [15]. The role of apoptosis in the potential increase of the BBB permeability by H. parasuis remains to be investigated, with the use, for example, of transwells as previously described [6].…”
Section: Discussionmentioning
confidence: 95%
“…Studies in the stratified squamous epithelium of the esophagus have presented evidence for the fact that acid stimulation disrupted the barrier function by modulating the amount and localization of TJ proteins in a cell culture model in vitro (3, 4, 25). Many studies in intestinal epithelial cell lines have also demonstrated that LPS could damage the intestinal epithelial barrier function by altering the TJ proteins expression and/or localization (5,13). Perhaps a more likely explanation is that, in the RE of goats, claudin-1 does not contribute to barrier function as it does in the colon (30) and esophagus (25) and that the loss of barrier function is due to the loss of claudin-4, occludin, and ZO-1.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we have shown that PAF does not only directly regulate apoptosis, but that signaling via the PAFR induces TLR4 expression in enterocytes (unpublished data). TLR4, the receptor for LPS, has been shown to take part in NEC pathogenesis [73,82], causes enterocyte apoptosis [101] and defective enterocyte migration [82]. Furthermore, TLR4 activation leads to induction of inflammatory molecules such as TNFα [102] and nitric oxide (NO) [103]; both of these molecules have been shown to be involved in NEC pathogenesis [15,81,104] and have been shown to be pro-apoptotic for enterocytes [81,105].…”
Section: Pro-apoptotic Signaling In Necmentioning
confidence: 99%